2020
DOI: 10.1098/rspa.2019.0741
|View full text |Cite
|
Sign up to set email alerts
|

Architecture and evolution of semantic networks in mathematics texts

Abstract: Knowledge is a network of interconnected concepts. Yet, precisely how the topological structure of knowledge constrains its acquisition remains unknown, hampering the development of learning enhancement strategies. Here, we study the topological structure of semantic networks reflecting mathematical concepts and their relations in college-level linear algebra texts. We hypothesize that these networks will exhibit structural order, reflecting the logical sequence of topics that ensures accessibility. We find th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 66 publications
0
26
0
1
Order By: Relevance
“…These networks exhibit core-periphery structure, indicating that they are composed of nodes that can roughly be divided into a densely-connected core and a periphery that is loosely connected to nodes within the core [46,47,48]. In addition, prior work has established that the periphery of these semantic networks possesses community structure [39]. Importantly, unlike modular networks, we find that the semantic networks are not very optimizable near β ≈ 0, but are significantly optimizable even for moderately Large values of β.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These networks exhibit core-periphery structure, indicating that they are composed of nodes that can roughly be divided into a densely-connected core and a periphery that is loosely connected to nodes within the core [46,47,48]. In addition, prior work has established that the periphery of these semantic networks possesses community structure [39]. Importantly, unlike modular networks, we find that the semantic networks are not very optimizable near β ≈ 0, but are significantly optimizable even for moderately Large values of β.…”
Section: Discussionmentioning
confidence: 99%
“…Still, it remains to be demonstrated that these results extend more generally to real-world information networks. To probe the optimal emphasis modulation strategies of real-world networks, we study semantic networks extracted from college-level linear algebra textbooks [39]. Specifically, nodes represent recurring concepts (e.g., "vector space", "invertible"), and edges between concepts are weighted by the number of sentences in which the two concepts co-occur.…”
Section: Optimizing the Learnability Of Semantic Network Extracted Fr...mentioning
confidence: 99%
See 2 more Smart Citations
“…The first study reports that science progresses as much through identifying uncharted gaps as through advancing solutions within scientific communities; the latter, filling-the-gap (or tessellating-the-cavity) discoveries are more frequently awarded Nobel prizes than discoveries adding edges at the boundaries of collective knowledge [74]. The second study reports that college-level mathematics textbooks are more likely to be rated highly on GoodReads when they progressively fill (rather than leave open) gaps in the knowledge network by connecting concepts introduced early with concepts introduced late [103]. Together, these studies suggest that there exist some domains of human inquiry where the act of placing a connection that fills a network cavity is more greatly valued than the act of placing a connection to the unknown at the frontiers of knowledge.…”
Section: Curiosity As Edgework Is Valuedmentioning
confidence: 99%